Efficient computation of adjusted p-values for resampling-based stepdown multiple testing - Joseph P. Romano; Michael Wolf (University of Zurich, Department of Economics, 2016)
There has been a recent interest in reporting p-values adjusted for resampling-based stepdown multiple testing procedures proposed in Romano and Wolf (2005a,b). The original papers only describe how to carry out multiple testing at a fixed significance level. Computing adjusted p-values instead in an efficient manner is not entirely trivial. Therefore, this paper fills an apparent gap by detailing such an algorithm.
Keywords: C12; 330; Adjusted p-values; Multiple testing; Resampling; Stepdown procedure